Cell wall biochemical alterations during Agrobacterium‐mediated expression of haemagglutinin‐based influenza virus‐like vaccine particles in tobacco. Issue 3 (5th January 2017) - Le Mauff, François; Loutelier‐Bourhis, Corinne; Bardor, Muriel; Berard, Caroline; Doucet, Alain; D'Aoust, Marc‐André; Vezina, Louis‐Philippe; Driouich, Azeddine; Couture, Manon M.‐J.; Lerouge, Patrice
Summary: Influenza virus‐like particles (VLPs) have been shown to induce a safe and potent immune response through both humoral and cellular responses. They represent promising novel influenza vaccines. Plant‐based biotechnology allows for the large‐scale production of VLPs of biopharmaceutical interest using different model organisms, including Nicotiana benthamiana plants. Through this platform, influenza VLPs bud from the plasma membrane and accumulate between the membrane and the plant cell wall. To design and optimize efficient production processes, a better understanding of the plant cell wall composition of infiltrated tobacco leaves is a major interest for the plant biotechnology industry. In this study, we have investigated the alteration of the biochemical composition of the cell walls of N. benthamiana leaves subjected to abiotic and biotic stresses induced by the Agrobacterium ‐mediated transient transformation and the resulting high expression levels of influenza VLPs. Results show that abiotic stress due to vacuum infiltration without Agrobacterium did not induce any detectable modification of the leaf cell wall when compared to non infiltrated leaves. In contrast, various chemical changes of the leaf cell wall were observed post‐ Agrobacterium infiltration. Indeed, Agrobacterium infection induced deposition of callose and lignin, modified the pectin methylesterification and increased both arabinosylation of RG‐I side chains and the expression of arabinogalactan proteins. Moreover, these modifications were slightly greater in plants expressing haemagglutinin‐based VLP than in plants infiltrated with the Agrobacterium strain containing only the p19 suppressor of silencing.